Inclusion in greek initial vocational education and training (IVET): The case of gendered language and socio-pragmatic strategies in promotional VET material - Christopher James Lees; Anastasia Pouliou (Publications Office of the European Union, 2025)
The purpose of this working paper is to examine the use of gendered language and socio-pragmatic strategies which appear in the Greek Ministry of Education's promotional VET material encouraging young people to take up an IVET course. It is related to Cedefop's research on the Future of VET which aims to deepen its understanding of the interaction between the broad objectives of excellence and inclusion in the 21st century. By using methods from sociolinguistic ethnography and discourse analysis, the authors examine the ways in which gendered language and language practices related to the target group are used in the material. Moreover, the attitudes of prospective IVET students at HQF/EQF level 4 are elicited through a semi-structured questionnaire carried out with a Greek secondary education school. Finally, specific recommendations are presented against the background of the EU's commitment to inclusive access to education.
Keywords: 370; Access to education and training; Attractiveness of vocational education and training (VET); Disadvantaged group; Initial education and training; Social inclusion; Vocational education and training; vocational training; vocational guidance; linguistics; gender mainstreaming; information analysis; use of languages; vocational education; Greece